Manajemen Strategi Dakwah MWCNU Ketapang Kabupaten Sampang dalam Memperkuat Nilai-Nilai Aswaja Al-Nahdliyah: Perspektif Manajemen Strategi Mintzberg - Ubaidilah Ubaidilah; Muhammad Yahya; Badrudin Badrudin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to describe and analyze the da'wah strategy implemented by the Nahdlatul Ulama Branch Representative Council (MWCNU) Ketapang, Sampang Regency, in strengthening the values ​​of Ahlussunnah wal Jama'ah al-Nahdliyah using the perspective of Henry Mintzberg's strategic management theory. This study uses a qualitative approach with field research. Data collection techniques are carried out through in-depth interviews, observation, and documentation. The results show that the MWCNU Ketapang da'wah strategy is implemented through two approaches, namely a cultural approach and a structural approach. The cultural approach is carried out through the preservation of local religious traditions such as tahlilan, maulidan, yasinan, and istighotsah. This approach is considered effective because it is in accordance with the characteristics of the Madurese community who are religious and have strong ties to religious traditions. Meanwhile, the structural approach is carried out through strengthening da'wah institutions, the establishment of formal da'wah institutions (LDNU), and cooperation between banom in socio-religious activities. Analysis using Mintzberg's theory shows that the MWCNU Ketapang's da'wah strategy encompasses five strategic dimensions: plan, ploy, pattern, position, and perspective. This strategy is adaptive, consistent, and oriented toward preserving the Aswaja values. The main supporting factors for the strategy's success are the role of kiai (Islamic scholars) and community support, while the inhibiting factors are the lack of digital da'wah innovation and the weak regeneration of young cadres. This study confirms that the success of NU da'wah at the local level depends heavily on the organization's ability to manage its strategy in a planned and contextual manner in accordance with the values ​​of Aswaja al-Nahdliyah.